Analysis of high dividend stocks listed on Singapore exchange - Chiranjiv Sawhney. (2011)
The following report has been designed to analyze stocks with high dividend yield listed on Singapore Exchange. Though two separate schools of thought, this project has used both fundamental analysis and technical analysis techniques to obtain the results. On discussion and deliberation, the author has chosen companies from different sectors of the market for the report. This will provide the author with a more comprehensive understanding of companies with high dividend yield stocks. The companies have been chosen according to a number of factors such as scope for industry growth, government backing preventing low market penetration, competition in the sector, brand presence etc. The companies chosen by the author are SingTel, M1, StarHub, SingPost, ST Engineering, ComfortDelgro and SMRT. Upon the fundamental and technical analysis of each company listed above, the author has tried to reach a conclusion about each company giving back-tested results and future recommendations. The report also enables one to figure out which is the best technique for an investor to beat the market – relying on fundamental analysis, on technical analysis or on a combination of both. The author thoroughly enjoyed his experience of analyzing these stocks and hopes that the reader enjoys his/her experience.